Faktor Yang Mempengaruhi Pertumbuhan Laba BANK Pembangunan Daerah Kawasan Timur Indonesia - Arzah Hidayatullah; Rabihatun Idris; Muhammad Irfai Sohilauw (Forum Kerjasama Pendidikan Tinggi, 2022)
This study aims to analyze the flow of Net Interest Margin (Nim) and Non Performing Loans (NPL) on Profit Growth from Regional Development Banks in Eastern Indonesia for the 2015-2020 period. This research is a quantitative research based on the philosophy of positivism. The population of this study consisted of 6 companies using the saturated sampling method with details of 6 x 6 = 36 units of data. Multiple linear regression analysis was used to analyze the effect of Net Interest Margin and Non Performing Loan on Profit Growth using SPSS v.23 software. The test results show that Net Interest Margin has a negative and significant effect, while Non-Performing Loans have a negative and significant effect on Profit Growth